A CONCEPTUAL STUDY OF DIET IN GRAHANI WITH SPECIAL REFERENCE TO MALABSORPTION - Nitesh, Joshi (International Journal of Ayurveda and Pharma Research, 2015)
Grahani which is the site of Agni, is so called because of its power to restrain the downward movement of undigested food and retains food till it is fully digested. Functionally weak Agni i.e. Mandagni, causes improper digestion of ingested food, which lead to Amadosha and it has pivotal importance in the pathogenesis of Grahani Roga. The main symptoms of Malabsorption are diarrhoea, loss of appetite, anorexia, and emaciation. The principle of diet for all types of Grahani is boost the Agni and reduce the Ama with the help of Ahara Dravyas, which included mainly Kashaya, Madhura and Katu in Rasa; Laghu, Ruksha, Grahee, Deepana and Pachana in Guna; Ushna in Veerya and Katu or Madhura in Vipaka. The diet regime suggested by Ayurveda helps in stimulation of Agni, which supports the digestion of food of appropriate quality, taken in required quantity and in right time for cure of Grahani Dosha or Malabsorption. The 28 Ahara Dravyas of various classes studied in this research can be suggested for Grahani patients. Thus we can resume the bowel habit to normal, improve the overall nutritional status of patients and can prevent or reduce the complications of Malabsorption with the help of Ayurvedic principles of diet.